Differential Effects of Agency, Animacy, and Syntactic Prominence on Production and Comprehension: Evidence From a Verb-Initial Language. - Bondoc, Ivan Paul; Schafer, Amy J. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2022)
Effects of animacy and agent prominence in linguistic and cognitive processing are well-established in the literature. However, it is less clear how strongly an agent argument will influence production and comprehension when a sentence also contains another prominent argument.We examine this question with Tagalog, a verb-initial language, which designates a syntactically prominent, subject-like element (the pivot) without demoting the grammatical status of the core agent. We implemented two experiments that investigated the influences of agent and pivot prominence on syntactic linear word order patterns in production and on anticipatory gaze patterns in comprehension. Tagalog's grammar allowed us to separate the influence of agentivity from animacy by manipulating the animacy of the pivot (animate pivots: agent and benefactive voices; inanimate pivots: patient and instrument voices). The production results contrasted with the comprehension results: agent and pivot prominence both emerged strongly in a fragment-completion production task, but animacy dominated anticipatory gaze patterns in a visual-world comprehension task. The results of these experiments demonstrate variability in production and comprehension outcomes as well as an apparent mismatch between the constraints that shape these two systems, which we attribute to contrasting goals in production versus comprehension and to the organization of information in verb-initial languages. The investigation highlights the value of research on languages with typologically understudied structural properties in revealing mechanisms of the production and comprehension systems.